A conceptual framework for crowdsourcing in higher education. - Shongwe, Thulani W. (My University, 2018)
The speedy growth of Internet based information and communication tools produced a new field of prospects for educational organizations to reach their aims. One of the options is crowdsourcing. Crowdsourcing was recently the answer to the growth for providing different applications in areas such as education, financing, and entrepreneurship. South African schools are considerably failing in education. A big challenge is when it comes to the mathematics delivery method which ends up affecting the learners’ performance. When compared to other middle income nations, South Africa is ranked third from the bottom in terms of its performance when it comes to mathematics. This study designed a conceptual crowdsourcing tutoring framework. The framework defines the use of how crowdsourcing can contribute to tutoring grade 11 and 12 mathematics in order to improve the learners’ performance. A prototype was developed to illustrate the crowdsourcing tutoring framework. The simpleKmeans algorithm was used in the prototype. The algorithm was used to select learners, tutors and appropriate textbooks for the virtual class. The prototype system proved to be effective as it was able to cluster students according to their performance and tutors according to their student pass rate. Through the usage of a clustering simpleKmeans algorithm, this study was able to create a virtual class that illustrated how all the components come together for the proposed crowdsourcing tutoring virtual class. The use of the prototype system was able to fill the virtual class with students who obtained low average marks and educators with the pupils who had the highest pass rate. This study was able to build a virtual class with the following components: learners, tutors and textbooks. Objectives and research questions of this study were fulfilled. In future studies the researcher will endeavor to make the system recommend textbooks without using the textbooks used by the teachers who produced the best results.
M. Tech. (Department of Information and Communication Technology, Faculty of Applied and Computer Technology) Vaal University of Technology.
Keywords: Crowdsourcing; Education; E-leaning; Dissertations, Academic -- South Africa.; Education, Higher -- South Africa.; Crowdsourcing.